Background and Rationale for the Need for the Fan Model, and Philosophical Views – Fan Science - Adinda Imamatul M; Kurdiyansah Kurdiyansah; Lusiana Lusiana; Listiani Listiani; Nadya Zafira S; Riza Bela H; Rusmiyati Rusmiyati (Feelings: Journal of Counseling and Psychology, 2026)
The KIPAS Counseling Model (Intensive, Progressive, Adaptive, and Structural Counseling) was developed in response to the growing demand for counseling services in Indonesia that are contextual, religiously rooted, and culturally relevant. This model integrates Islamic values, local wisdom, and modern psychological principles into a holistic and dynamic counseling framework. This study uses a literature review method to explore the background, rationale, and philosophical-scientific foundations underlying the KIPAS model. The approach not only addresses psychological issues but also aims to shape character, strengthen self-identity, and foster spiritual awareness. From the perspective of philosophy of science and human nature, this model highlights the importance of glocalization and postmodern approaches in advancing guidance and counseling knowledge. Therefore, the KIPAS model provides a comprehensive, ethical, and culturally responsive solution for counseling practices in Indonesia.